Niat beli konsumen: Pengaruh green brand dan green knowledge pada industri jamu dan farmasi Sido Muncul Tbk - Fauzan , Rizky Sani; Widodo , Arry (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to determine the role of green knowledge as a mediator between the green brands of PT Industri Jamu and Sido Muncul Tbk with consumer intentions to make purchases. This study used the non-probability incidental sampling method and the Likert scale for quantitative analysis according to the Theory of Planned Behavior (TPB). This study used structural equation modeling (SEM-PLS) to analyze the data, and SmartPLS was used to process the SEM-PLS. Data. The results of the hypothesis test show that green branding has a positive effect on green knowledge. This indicates a positive and statistically significant relationship between green brands and green expertise, and there is a positive relationship between green brands and green purchase intention. It is known that the to-value green knowledge affects purchase intention, so it can be concluded that green brand has a positive and statistically significant impact on consumer tendencies to make purchases. This shows that environmental literacy significantly affects consumer tendencies to buy. The result is to value green brands' effect on knowledge-mediated purchase intent. Therefore, green knowledge serves as a mediator between a green brand and consumers' desire to buy.